2021
DOI: 10.1101/2021.07.01.450750
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Strong phylogenetic signal despite high phylogenomic complexity in an Andean plant radiation (Freziera,Pentaphylacaceae)

Abstract: The Andes mountains in South America are a biodiversity hotspot within a hotspot, the New World Tropics, for seed plants. Much of this diversity is concentrated at middle-elevations in cloud forests, yet the evolutionary patterns underlying this extraordinary diversity remain poorly understood. This is partially due to a paucity of resolved phylogenies for cloud forest plant lineages: the young age of the Andes and generally high diversification rates among Andean systems precludes robust phylogenetic inferenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 203 publications
(393 reference statements)
2
6
0
Order By: Relevance
“…As gene duplication and loss is one of the sources of gene tree discordance (Degnan & Rosenberg, 2009), discriminating between orthologues and paralogues is likely to reduce gene tree discordance, which we indeed observed in the case of our two Malinae data sets (Figure 3). ParalogWizard did, however, not increase the proportion of concordant nodes for the Oritrophium and Amomum data sets, which is in line with Gardner et al (2021) and Frost and Lagomarsino (2022), who found that gene tree discordance increased when paralogous loci were added.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…As gene duplication and loss is one of the sources of gene tree discordance (Degnan & Rosenberg, 2009), discriminating between orthologues and paralogues is likely to reduce gene tree discordance, which we indeed observed in the case of our two Malinae data sets (Figure 3). ParalogWizard did, however, not increase the proportion of concordant nodes for the Oritrophium and Amomum data sets, which is in line with Gardner et al (2021) and Frost and Lagomarsino (2022), who found that gene tree discordance increased when paralogous loci were added.…”
Section: Discussionsupporting
confidence: 86%
“…We developed an approach to minimize the removal of entire loci and to, instead, use biologically real loci in target enrichment data sets. This is in line with Frost and Lagomarsino (2022), who promote the use of well curated data for phylogenomics. We first detect multicopy loci, then evaluate the pairwise sequence similarity of their exons, followed by a check for multimodal distribution, which is used to discriminate between a main and secondary copy (Figure 1).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Universal probe sets for target capture such as the GoFlag angiosperm 408 probes used in this study (Endara and Burleigh, 2022), Angiosperm 353 (Johnson et al, 2019), and ultraconserved elements (UCEs; McCormack et al, 2012) are designed to target sequences from an evolutionarily broad group of organisms and thus may be also more likely to recover contaminant sequences than clade-specific probe sets. Additionally, while the GoFlag angiosperm 408 probes (and most other universal probe sets) target single-copy nuclear genes, these regions were identified as single-copy at a broad evolutionary scale (all angiosperms), which cannot ensure that recent gene duplications have not occurred within our target group (Frost and Lagomarsino, 2021). While one option may be to design more clade-specific probe sets, this is not feasible for many researchers—including for us in this study—and may negate the potential data-sharing benefits of global probe sets (depending on the way clade-specific probe sets are generated).…”
Section: Discussionmentioning
confidence: 99%